Oriental passion to honor the dead - Gutierrez, Ana Ruiz (2013)
To promote the expiation of sins committed on earth, pious donations were common; the chaplaincy was the more common religious foundation, which was intended to secure in perpetuity a number of votes for the eternal repose of the soul of the patron or patrons. To ensure its continued maintenance, material goods were provided; these goods, together with the owner, are generally exhibited in their funerary chapels. Because of the Manila Galleon, which led to the exchange of Asian goods between East and West, it is thus very common to find works from Asia, China, Japan, and the Philippines in the decor of these funerary chapels.
Keywords: Galleons -- Manila; Grave goods; Funeral decorations